BREAKING DISCIPLINARY BOUNDARIES: INTERDISCIPLINARITY FROM SCIENCE TO THE CLASSROOM - de Alencar, Adna Rodrigues; Almeida, Antonio Werbiton Marinho; Castro, Argentina Mororó; da Costa, Ernandes Farias; de Melo, Erica Cristina Machado; Franklin, Francisca Elsa Silva; Costa, Ilcimar Gomes Vieira; Fontes, Irene Mendes; Junior, Juvanildo Terra de Alencar; Amaral, Lilian do Socorro Viana e Viana; Xavier, Régia Maria Carvalho; Gomes, Rickardo Léo Ramos (Seven Editora, 2024)
The concept of interdisciplinarity has become essential in contemporary education, particularly in a world where social, economic, and environmental issues are increasingly complex and interconnected. There is a clear need for a strategy that integrates diverse fields of knowledge, as many challenges cannot be understood or solved from a single discipline alone. Conventional education, often compartmentalized, may restrict students' ability to think critically and solve problems effectively. Therefore, encouraging interdisciplinary practices in the classroom is crucial to equip students for a dynamic and multifaceted future. This study employed a qualitative methodology and utilized a literature review as a research method, which was vital for fostering dialogue with researchers specialized in the same topic discussed herein. The general objective of this research was to explore and examine the relevance of interdisciplinarity in contemporary education, highlighting how the integration of various fields of knowledge can enhance the teaching-learning process and prepare students to address the challenges of an ever-changing world. The study underscored the importance of uniting multiple areas of knowledge to cultivate critical, creative citizens ready to collaborate in an increasingly complex global context. Therefore, it is imperative that educators and educational institutions adopt interdisciplinary practices, promoting a more cohesive and relevant education for all students. DOI:https://doi.org/10.56238/sevened2024.021-011